2022-RA-1043-ESGO CT-guided percutenous radiologic gastrostomy in heavily pretreated patients with late stage ovarian cancer: -the charité experiences-. (20th October 2022) - Canaz, Emel; Auer, Timo Alexander; Gebauer, Bernhard; Sehouli, Jalid
Abstract : Introduction/Background: Peritoneal carcinomatosis-associated ileus is frequent in advanced-recurrent ovarian/peritoneal/fallopian cancer and affects the quality of life due to severe symptoms of obstruction.CT-guided insertion of percutaneous gastrostomy (CT-PG) is a new minimal-invasive treatment option within the palliative management of gynaecological cancer patients. Methodology: Based on retrospective analysis we evaluated 18 patients undergoing percutaneous radiologic gastrostomy between September/2015 and April/2022. Clinical characteristics, complications, symptom-relief, need of secondary interventions and surgery for ileus, ability of receiving chemotherapy and mortality were identified.CT-guided gastrostomy was applied by Seldinger technique in local anesthesia. Results: The indication of CT-PG was peritoneal carcinomatosis-associated ileus in all patients. 15-patients had already undergone a frustrating endoscopic gastrostomy (PEG) placement or ileus operation prior CT-PG insertion.CT-PG could be successfully placed at 14 patients without any major interventional complication other than a local bleeding which was conservatively managed. The commonly observed metabolic complication after insertion was hypokalaemia requiring parenteral substitution. Symptom relief: 10 of 14 patients who had successful CT-PG showed considerable symptom relief without need of any other subsequent invasive interventions other than one CT-PG re-insertion. Almost in all patients (13) surgery for ileus could be safely omitted.Only 3 patients needed additional PEG-insertion by gastroscopy due to inefficient flow-rate of radiologically inserted gastric-tube.Prognosis: 30-days mortality including patients who lost-to-follow-up in all intention-to-threat-population was 72% (13/18) with observed 5-events. Mean hospital stay after successful placement was 9.9 days(2–27 days). Chemotherapy could be administrated in 3 patients; however only 1 patient with primary diagnosis could receive 3-cycles of neoadjuvant chemotherapy.All other patients had been managed according to best-supportive-care principles due to high frailty and were placed on hospice/palliative station shortly after receiving gastrostomy. Conclusion: The CT-PG is minimal invasive, safe, highly symptom-oriented palliative procedure in advanced/recurred peritoneal cancer. CT-PG procedure should be a routine instrument in the palliative management of bowel obstruction in patients with heavily-pretreated ovarian cancer.